Flash vacuum pyrolysis (fvp) of some hexahydroquinazolin-4(1H)-ones - Peláez, Walter José (2008)
—Some cis/trans-2-thioquinazolin-4-ones and their 2,4-dione analogs were subjected to flash vacuum pyrolysis. The cis- and trans-thio compounds reacted at lower temperatures than the cis- and trans-dioxo analogs, showing a lower thermal stability. All of these compounds afforded similar reactions: ring opening to the corresponding iso(thio)cyanate, the loss of H and NCS to form three isomeric cyclohexadienes and then aromatization to form the corresponding benzamide. The cis-dioxo compound also underwent a competitive retro Diels–Alder (RDA) reaction to form 3-phenylpyrimidine-2,4(1H,3H-dione(3-phenyluracil)) and butadiene. Kinetic measurements of the ring opening reaction supported a concerted b-elimination as the most probable mechanism.